Event driven technology intelligence - Song-Kyoo Kim (Journal of Economy and Technology)
The Event Driven Technology Intelligence (EDTI) model offers a structured approach to navigating the complexities of technological innovation. This research aims to summarize the core concepts and phases of the EDTI model while also exploring its significance in various industries. By expanding on the traditional Hype-cycle model to include seven phases, EDTI guides companies from concept innovation through product execution. Crucial to this model are the Moments-of-Event which represent key breakthroughs necessary for advancing technologies. By integrating these insights, EDTI enhances decision-making, fosters innovation, and mitigates risks associated with technology obsolescence, ultimately helping organizations adapt to changing consumer demands and maintain competitiveness in dynamic markets. In the rapidly evolving landscape of technology, the EDTI model emerges as a vital tool for organizations striving to remain competitive. This model flourishes in a climate marked by global competition and the constant demand for innovation. Key to its success is the integration of critical events and technological breakthroughs, which allow businesses to effectively manage and leverage emerging technologies.